The application of the Everyone is a Teacher Here (ETH) Learning Model to the Learning Outcomes of Students in Class XI F5 in History Subjects at SMAN 1 Kec. Lareh Sago Halaban in the 2023/2024 School Year. - Putri, Khairani Destel; Meri, Destel; Asmara, Dedi (Riwayat: Educational Journal of History and Humanities, 2025)
This research is motivated by the use of the lecture method makes the learning process less interesting and learning seems boring so that students pay less attention to the lesson, then it causes low student learning outcomes. The formulation of the problem of this study is to determine the effect of the application of the everyone is a teacher here learning model on the history learning outcomes of students in class XI F5 SMAN 1 Kec. Lareh Sago Halaban and the difference in the effect of the application of the everyone is a teacher here learning model on the history learning outcomes of students in class XI F5 SMAN 1 Kec. Lareh Sago Halaban. This research is a quantitative research using experimental method with research design of nonequivalent control group design. The sampling technique was taken by simple random sampling. The data taken is the learning outcomes of the experimental class and the control class. The data analysis technique used is the t-test, by doing the normality test and homogeneity test first. The results showed: 1) there is an effect of everyone is a teacher here learning model on student learning outcomes in history subjects with the value of Tcount = 3,885 and Ttable at a significant level of 0.05 is 1.675, meaning Tcount Ttable. 2) there is a difference in the effect of the everyone is a teacher here learning model and the conventional learning model on learning outcomes. Thus it can be concluded that there is an effect of the application of everyone is a teacher here learning model on student learning outcomes in history subjects in class XI F5 at SMAN 1 Kec. Lareh Sago Halaban